Legal Aid and Human Rights : A Reflection - Alex Chandra (fakultas hukum universitas PGRI Semarang, 2023)
Humanity and Human Rights is a concern of mankind throughout the world. Therefore, the consequences if there is a violation of human rights anywhere in the world will be a concern for humans everywhere in this world. The difficulty that is faced with this